THE EFFECT OF ROAD DAMAGE ON GREENHOUSE GAS EMISSIONS (CASE STUDY OF KENDAL EASTERN HIGHWAY) - St Marisa Haq; Ary Setyawan; Fajar Srihandayani (RADJA PUBLIKA, 2026)
This article describes how road damage affects greenhouse gas (GHG) emissions. The object of this study is the 2 km East Kendal National Road, divided into 40 segments. To measure road damage, the Pavement Condition Index (PCI) method was used, while to measure greenhouse gas emissions, the IPCC (Intergovernmental Panel on Climate Change) method was used. There are three important findings in this study. First, the East Kendal National Road section is generally in poor to very poor condition with an average Pavement Condition Index (PCI) value of 33.83. Second, road damage affects the average speed of vehicles. Third, vehicle speed affects the amount of GHG emissions. When vehicle speed decreases due to road damage, fuel efficiency is reduced, so that CO₂, CH₄, and N₂O emissions increase. The results of the correlation analysis show a value of R = 0.648 for CO₂, R = 0.613 for CH₄, and R = 0.613 for N₂O, which means there is a fairly strong positive relationship between the level of road damage and greenhouse gas emissions. The conclusion is that the lower the PCI value (the more severe the road damage), the lower the average vehicle speed, and the lower the PCI, the higher the GHG emissions, namely CO₂, CH₄, and N₂O.